Pengaruh Model Pembelajaran Teams Games Tournament Berbasis HOTS Terhadap hasil Belajar Peserta Didik Mata Pelajaran Matematika di Kelas V SD Negeri Madyotaman Surakarta Tahun Pelajaran 2023/2024 - Nida' Mu'azaroh Khoiriyah; Sri Handayani; Elinda Rizkasari (Jurnal Riset Pendidikan Dasar (JRPD), 2024)
Learning models can influence student learning outcomes. The aim of this research is to find out whether there is an influence of the HOTS-based Teams Gemes Tournament (TGT) learning model on student learning outcomes in Class V of SD Negeri Madyotaman Surakarta for the 2023/2024 academic year. This type of research is quantitative research using a pre-experimental method with one group pretest-posttest research. The results of data analysis using the Teams Games Tournament learning model based on HOTS show that the average pretest score for students is 47.96 and the posttest score is 67.19. After using the paired sample t-test, the results obtained are tcount with ttable using dk = (N -1) then (26-1) = 25 at the 5% significance level, it can be concluded that tcount>ttable or 20,670 > 2,060 which means Ha is accepted and Ho is rejected. So it can be concluded that this research shows the influence of the HOTS-based Teams Games Tournament (TGT) learning model on the learning outcomes of Mathematics subject students in class V of Ngeri Madyotaman Elementary School, Surakarta.